2010
DOI: 10.1086/649792
|View full text |Cite
|
Sign up to set email alerts
|

Focus Group Study of Hand Hygiene Practice among Healthcare Workers in a Teaching Hospital in Toronto, Canada

Abstract: Our results confirm previous findings that hand hygiene is practiced for personal protection, that limited access to supplies is a barrier, and that role models and a sense of team effort encourage hand hygiene. Educating HCWs on how to manage workload with guideline adherence and addressing contaminated hospital equipment may improve compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
96
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 29 publications
(14 reference statements)
14
96
2
3
Order By: Relevance
“…This links with other studies regarding role models and the importance of having good role models for hand hygiene on sites to champion hand hygiene for others (Jang et al, 2010, Dixit et al, 2012. Feather et al (2000) found that medical students were modelling the poor hand hygiene practices of medical personnel.…”
Section: Discussionsupporting
confidence: 72%
“…This links with other studies regarding role models and the importance of having good role models for hand hygiene on sites to champion hand hygiene for others (Jang et al, 2010, Dixit et al, 2012. Feather et al (2000) found that medical students were modelling the poor hand hygiene practices of medical personnel.…”
Section: Discussionsupporting
confidence: 72%
“…3 Furthermore, many studies done to assess the knowledge, attitudes, compliance and reasons for non-adherence to hand hygiene guidelines have found that compliance with hand hygiene protocols by health care workers (HCW) is poor 4,5,6 due to several constraints, including heavy work load, high number of clinical procedures and skin conditions of the HCW. 7,8 An alarming revelation was that compliance was found to be worst before highrisk procedures. 5,9 In Asia there is a paucity of studies 10,11,12 exploring this subject, although the prevalence of health care associated infections is high in this region.…”
Section: Introductionmentioning
confidence: 99%
“…7 Healthcare workers may feel that wearing gloves not only protects them from the pathogens on patients but also protects patients from the pathogens on healthcare workers' hands 30,31 and that this obviates the need for hand disinfection. Hand hygiene behavior has been classified as being either inherent (motivated by feelings of disgust, after contact with dirt or perceived dirt) or elective (not motivated by disgust).…”
mentioning
confidence: 99%